Perencanaan dan Pembuatan Sistem Informasi Administrasi dengan Inventory Control Pada Perusahaan Mie Ikan Mas - Valentina Winda Kristianti; Djoni Haryadi Setiabudi; Zeplin Joshua Tarigan (Jurnal Infra, 2015)
Administration Information System in Ikan Mas Company is still using manual system. The number of customer order often make company difficult to control their inventory stock. That makes the stock of raw materials they have always run into stock out. The company also have difficulty because the uncertain supplier.To overcome these problem, we need a new system that can replace the old system and change the manual system into computerize system. System that will be create such as recording sales, purchasing, production, recording the entire master data, calculation of the raw and finished materials stock, and also a report purchase, sales and income statement.Results of making this program is to optimize the entire collection of raw materials and finished materials, recording purchase and sales as well as production.